Heating experiments with palm olein and groundnut oil - Augustin, M.A. (2013)
The quality changes in refined, bleached and deodorized palm olein (RBD olein) and groundnut oil during static heating at 180 degrees C for 5h. per day for 8 consecutive days were studied. The indices used for assessment of oil quality included percent polar components, dielectric constant, polymer content, E ('1 percent)(,1 cm) at 232 and 268nm, iodine value, C18:2/C16:0 ratio if glyceride-bound fatty acids, colour acid value and smoke point. The results showed that the major differences between the performance of the oils were that (i) groundnut oil was more susceptible to the formation of polymers and (ii) RBD olein was more prone to darkening than groundnut oil. The results also suggest that darkening of RBD olein cannot be solely linked to qua1983lity deterioration of the